Remediation of Sexual Violence of The New Order Regime in The Film of Seperti Dendam Rindu Harus Dibayar Tuntas - Indriani, Laillia Dhiah (Capture : Jurnal Seni Media Rekam, 2023)
Sexual violence has become a hot topic of discussion recently. However, it didn’t just happen; sexual violence has roots in a long history in Indonesia. Every regime has its narrative of sexual violence, and the New Order regime is no exception. The New Order, often labeled as a military and violent regime, could not detach itself from the "sexual violence" issue. The sexual violence that characterized the New Order regime was depicted in realistically in the film "Seperti Dendam Rindu Harus Dibayar Tuntas," which was adapted from a novel with the same title. This research tried to dismantle the practice of sexual violence in the New Order regime, which was remedied in the film "Seperti Dendam Rindu Harus Dibayar Tuntas." It also examined how it related to the initial narrative contained in the novel and reality. The type of descriptive qualitative research used. The theoretical framework used was the remediation concept. Data were collected through a literature review and documentation, then further analyzed using Alan McKee's textual analysis technique. The results of this study show that not only women but also men undergo sexual violence. Additionally, The remediated film focuses more on the trauma of victims of sexual violence, both women and men. Keywords: New Order, sexual violence, novels, films.